2020
DOI: 10.1007/s00268-020-05786-7
|View full text |Cite
|
Sign up to set email alerts
|

Getting it Right the First Time: Frozen Sections for Diagnosing Necrotizing Soft Tissue Infections

Abstract: Background The aim of this study was to investigate which histopathologic findings are most indicative for necrotizing soft tissue infections (NSTIs) in ambivalent cases. Methods Patients undergoing surgical exploration for suspected NSTIs with obtainment of incisional biopsies for histopathological assessment were included from January 2013 until August 2019. The frozen sections and formalin-fixed paraffin-embedded (FFPE) samples were retrospectively re-assessed. The primary outcome was the discharge diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The use of intra-operative diagnostics such as frozen section or Gram stain have also been argued to cause treatment delay, since the time waiting on the results could also be used for debridement, however this statement was not yet investigated in a clinical study [ 24 , 25 ]. This study found indeed a prolonged operative time with a difference in medians of 41 min, which is to be expected since it can take up to 30 min to process and assess a frozen section [ 12 , 13 ]. However, the time to diagnosis was significantly shorter in cases that used intra-operative diagnostics (difference in medians of 3 h), which enables timely debridement.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The use of intra-operative diagnostics such as frozen section or Gram stain have also been argued to cause treatment delay, since the time waiting on the results could also be used for debridement, however this statement was not yet investigated in a clinical study [ 24 , 25 ]. This study found indeed a prolonged operative time with a difference in medians of 41 min, which is to be expected since it can take up to 30 min to process and assess a frozen section [ 12 , 13 ]. However, the time to diagnosis was significantly shorter in cases that used intra-operative diagnostics (difference in medians of 3 h), which enables timely debridement.…”
Section: Discussionmentioning
confidence: 70%
“…NSTI refers to the necrotizing forms of fasciitis, myositis and cellulitis. The NSTI had to be confirmed by either operative findings and/or histopathologic tissue findings and/or microbiology results [ 12 , 13 ]. Patients younger than 18 years at time of onset of the NSTI were excluded, as well were patients who were lost to follow-up after their initial debridement (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid histopathologic assessment or consideration of use of frozen sections and/or intraoperative gram stain should be considered. 5 Alternatively, if the suspicion for nSS is high and debridement is not pursued, a punch biopsy of adjacent indurated, but non-necrotic skin, may be performed. In typical necrotizing fasciitis ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Fifty microliters of a rabbit polyclonal antibody against Iba1 (Abcam; ab178846, 1:100) was dropped onto each brain tissue and incubated overnight at 4°C. (6) The tissues were rinsed with PBS buffer for 3 min × 3 times. (The longer the culture time or the thicker the section, the longer the rinse time.)…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%